General-leutnant Dr Karl Mauss (1898-1959) - Xavier Riaud (Journal of Dental Problems and Solutions - Peertechz Publications, 2017)
After it has invaded Poland, Germany will have to carry on paying the bills for Hitler's expansion projects. Thus, thousands of men will die on the battle fields. Many more will come back crippled. A lot of men abuse their power over the civilian populations of the occupied territories. Throughout these battles, true personalities got revealed and, although one might think that true courage would have been to resist and fight against the Nazi government, some of men have distinguished themselves on the battle fields. Dentists were no exception. The following story deals with one of them.